Perancangan Alat Pendeteksi Asap dan Suhu Ruangan Berbasis Internet Of Think di PT. APAC Inti Corpora - Indra Ava Dianta; Moh Muthohir; Ilham Ramasyahdani; Fatkhul Amin (Elkom : Jurnal Elektronika dan Komputer, 2022)
In this final project the author discusses the problem entitled "Design of Smoke Detector and Room Temperature of SAP ERP Server at PT Apac Inti Corpora". This design aims to support the improvement of the security system in the server room with smoke and temperature detectors and microcontroller-based automatic countermeasures. Against the background of problems with sensors and countermeasures systems in the server room and lack of insight into sensor installation. This tool uses a gas sensor MQ-2 as a smoke detector, a DHT-11 sensor as a temperature detector, Arduino as a microcontroller that controls I/O, buzzer and LED as an alarm, a fan as a temperature controller, and an LCD to display conditions in the room. The output of the MQ-2 and DHT-11 sensors will be processed in a programmed microcontroller so that it can display conditions on the LCD. This tool will turn on the alarm and fan if smoke and high temperature are detected at the specified conditions.